Anti-Toxoplasma gondii antibody detection in serum and urine samples by enzyme-linked immunosorbent assay in HIV-infected patients - Sayan Bhattacharyya; Sumeeta Khurana; Mohan Lal Dubey (Wolters Kluwer Medknow Publications, 2013)
Background: Toxoplasmosis is a common parasitic infection of man, and reactivation of latent disease in HIV-infected patients can cause fatal encephalitis. Diagnosis depends on demonstration of parasite-specific antibodies in serum. In HIV-infected patients, IgM is often undetectable, whereas IgG remains detectable in the majority. Urine sample is very easily available and has not been evaluated for immunodiagnosis of toxoplasmosis. Aim: The study was an effort to find whether urine sample can be used in place of serum for immunodiagnosis of toxoplasmosis. Materials and Methods: Enzyme-linked immunosorbent assay (ELISA) was carried out in serum and urine samples collected from 100 HIV-infected patients to detect anti-toxoplasma IgG and IgM antibodies and whether positivity correlated with the CD4 T-cell counts of patients. Results: In this study, we observed that there was no significant difference in positivity of anti-toxoplasma IgM and IgG between serum and urine samples of HIV-infected patients by ELISA. There was a negative correlation between CD4 count and seropositivity. Conclusion: Urine sample can be satisfactorily used in place of serum for immunodiagnosis of toxoplasmosis.